Dietary practices and anthropometric profile of professional male surfer - Lima Ribeiro, S.; Freitas, A. M. P.; Pereira, B.; Vilalva, R.; Krinski, K.; Souza-Junior, T. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There is a lack of information concerning nutritional status of surfers. This study has the aim to identify dietary practices together with anthropometric variables of a group of professional surfers. Methods: The voluntaries were recruited at a National Surf Championship in Brazil, and were evaluated for anthropometric measures, indexes and calculations (body mass, height, arm span, body circumferences and nine skinfold thicknesses, arm spam/height ratio, waist-to-hip-ratio, conicity index and % body fat). They answered a 24h food-recall, calculated by daily intake of energy, macro-nutrients, some micro-nutrients and food groups were analyzed. The values were compared with some references and position statements and with the Brazilian Food Guide. The daily basal energy expenditure, daily total energy expenditure and energy balance were predicted by specific equations. Results: - The intake of carbohydrate is below the position statements, at least considering the day before competition. However, possibly the intake of supplements such as maltodextrin fulfilled the requirements of some, but not all, the athletes; - The intake of BCAA showed to be high; - The low intake of vegetables possibly contributes to the low intake of micronutrients such as folic acid; - The high intake of fried food overlapped healthy habits such as nuts consumption; - The percentage of body fat seems to be similar to swimmers (around 12% of body weight). Discussion: This study certainly will contribute to the understanding of body composition and feeding practices of professional surfers. Further investigation, with more sophisticated methods of evaluation, could improve our findings.